A synthesis of the effect of grazing exclusion on carbon dynamics in grasslands in China. (6th January 2016) - Hu, Zhongmin; Li, Shenggong; Guo, Qun; Niu, Shuli; He, Nianpeng; Li, Linghao; Yu, Guirui
Abstract: Grazing exclusion (GE) is considered to be an effective approach to restore degraded grasslands and to improve their carbon (C) sequestration. However, the C dynamics and related controlling factors in grasslands with GE have not been well characterized. This synthesis examines the dynamics of soil C content and vegetation biomass with the recovery age through synthesizing results of 51 sites in grasslands in China. The results illustrate increases in soil C content and vegetation biomass with GE at most sites. Generally, both soil C content and vegetation biomass arrive at steady state after 15 years of GE. In comparison, the rates of increase in above‐ and belowground biomass declined exponentially with the age of GE, whereas soil C content declined in a milder (linear) way, implying a lagged response of soil C to the inputs from plant biomass. Mean annual precipitation (MAP) and the rate of soil nitrogen (N) change were the main factors affecting the rate of soil C content change. MAP played a major role at the early stage, whereas the rate of soil N change was the major contributor at the middle and late stages. Our results imply that the national grassland restoration projects in China may be more beneficial for C sequestration in humid regions with high MAP. In addition, increased soil N supply to grasslands with GE at the latter recovery stage may enhance ecosystem C sequestration capacity.